When order matters: Last-come first-served effect in sequential arithmetic operations - Zylberberg, Ariel Dario (2012)
Cognitive psychologists have relied on dual-task interference experiments to understand the low-capacity and serial nature of conscious mental operations. Two widely studied paradigms, the Attentional Blink (AB) and the Psychological Refractory Period (PRP) have demonstrated a first-come first-served policy; processing a stimulus either impedes conscious access (AB) or postpones treatment (PRP) of a concurrent stimulus. Here we explored the transition from dual-task paradigms to multi-step human cognition. We studied the relative weight of individual addends in a sequential arithmetic task, where number notation (symbolic/non-symbolic) and presentation speed were independently manipulated. For slow presentation and symbolic notation, the decision relied almost equally on all addends, whereas for fast or non-symbolic notation, the decision relied almost exclusively on the last item reflecting a last-come first-served policy. We suggest that streams of stimuli may be chunked in events in which the last stimuli may override previous items from sensory buffers.